2013
DOI: 10.1039/c3cy20728e
|View full text |Cite
|
Sign up to set email alerts
|

Emerging catalytic processes for the production of adipic acid

Abstract: Research efforts to find more sustainable pathways for the synthesis of adipic acid have led to the introduction of new catalytic processes for producing this commodity chemical from alternative resources. With a focus on the performance of oxygen and hydrogen peroxide as preferred oxidants, this minireview summarizes recent advances made in the selective oxidation of cyclohexene, cyclohexane, cyclohexanone and n-hexane to adipic acid. Special attention is paid to the exploration of catalytic pathways involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
222
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(229 citation statements)
references
References 197 publications
(229 reference statements)
1
222
0
6
Order By: Relevance
“…Selective catalytic catechol cleavage would nevertheless be advantageous, as hydrogenation 4 of the intradiol cleavage product, muconic acid (3a), can provide a greener route to adipic acid or its esters, which are key monomers, e.g., for nylon-6,6. 5 Such a route would make use of non-toxic catalysts and oxidants, be highly atomefficient and employ a renewable substrate, as catechol may be obtained sustainably from lignin 6 or by fermentation of glucose. Que et al have reported the most active system for stoichiometric intradiol cleavage of 3,5-di-tert-butylcatechol reported to date, using the ligand tris(2-pyridylmethyl)amine (tpa).…”
mentioning
confidence: 99%
“…Selective catalytic catechol cleavage would nevertheless be advantageous, as hydrogenation 4 of the intradiol cleavage product, muconic acid (3a), can provide a greener route to adipic acid or its esters, which are key monomers, e.g., for nylon-6,6. 5 Such a route would make use of non-toxic catalysts and oxidants, be highly atomefficient and employ a renewable substrate, as catechol may be obtained sustainably from lignin 6 or by fermentation of glucose. Que et al have reported the most active system for stoichiometric intradiol cleavage of 3,5-di-tert-butylcatechol reported to date, using the ligand tris(2-pyridylmethyl)amine (tpa).…”
mentioning
confidence: 99%
“…In parallel, other researchers [42,43] proposed cogeneration of fuels and chemicals. While producing biofuel requires a high degree of deoxygenation, the application of biomass for producing chemicals may potentially skip costly oxidative processes and provide viable pathways toward production of alcohols, carboxylic acids, and esters [44,45]. While these integrated biorefineries benefit from economies of scale and diversity of bioresources, they also face a challenge with respect to imbalanced product markets.…”
Section: H60322 O25828) Ismentioning
confidence: 99%
“…Industrial production of nylon 6,6 is mostly achieved by condensation of hexamethylene diamine and adipic acid (AA). Among DCAs, AA is produced most; its annual global production is prospected to reach 2.7 million tons in 2017 2 . Other DCAs have significantly smaller production volumes 3 ; due to the cumbersome production from petrochemical feedstocks.…”
Section: Transition To a Sustainable Industrial Chemistrymentioning
confidence: 99%
“…HMF is hydrogenated in a multistep process to yield 1,6-hexanediol. Unfortunately, the hydrogenation of HMF results in the formation of a significant amount byproducts and requires a high H2 pressure 2,74 .…”
Section: 61mentioning
confidence: 99%
See 1 more Smart Citation